Applications of peptide hormone ligands for the treatment of dumping and short bowel syndrome. (December 2018) - Wauters, Lucas; Vanuytsel, Tim
Highlights: Pasireotide, a novel somatostatin analogue, is effective in early and late dumping syndrome. GLP-1 analogues alleviate signs and symptoms of dumping syndrome. Teduglutide decreases the needs for parenteral support in short bowel syndrome. The effects of GLP-1 analogues in short bowel syndrome are promising. Abstract : Dumping syndrome is a common and debilitating complication of upper gastrointestinal surgery. Accelerated gastric emptying and dysregulated secretion of gastrointestinal (GI) hormones are involved in its pathophysiology. Pasireotide, a novel somatostatin analogue, improved dumping in a phase-2 study. Preliminary data suggest that the glucagon-like peptide-1 (GLP-1) analogue liraglutide can also improve dumping. Short bowel syndrome is the most common cause of intestinal failure and involves not only a loss of mucosal absorptive area but also hypersecretion and accelerated transit. GLP-2 is the best studied hormone involved in intestinal adaptation. An increasing body of evidence demonstrates that the GLP-2 analogue teduglutide reduces parenteral support needs. New GLP-2 analogues and analogues of other GI hormones such as liraglutide are being investigated as promising treatments in short bowel syndrome.